The analysis of J. Strassler’s “Idioms in English: A Pragmatic Analysis” - Ortikov Eldor Mardonovich (International Journal on Human-Computing Studies, 2021)
Strassler’s aims in Idioms in English: A Pragmatic Analysis, a book deriving from a doctoral thesis, are twofold: 1 The identification of idiom functions, hence Strassler’s choice of pragmatic theories in terms of which to analyse idiom use. 2 The identification of the special features of idioms which set them apart from the rest of the vocabulary, features which also constitute their raison. Strassler’s